A Study Of Malaysian Year 5 Pupils’ Pre-Algebraic Thinking - Gan , We Ling; Ghazali, Munirah (Penerbit Universiti Sains Malaysia, 2014)
This paper reports part of the findings of a study undertaken to investigate Malaysian Year 5 pupils’ pre-algebraic thinking while they were solving pre-algebraic problems. It focuses on the inference of pre-algebraic thinking among five 11-year-old pupils while solving three pre-algebraic problems involving geometric patterns. Data for this study was collected on a one-by-one basis, during which each participant was observed while solving the problems. While they were solving the problems, the participants were required to think aloud by verbalising whatever came to mind during the problem-solving process. After solving each problem, retrospective interviews were conducted if there was reason to think that additional information could be elicited from the participant. The think-aloud and interview sessions were audio-taped and transcribed. The verbatim transcripts were given to the participants to achieve a negotiated interpretation of the data. The verbatim transcripts were then segmented to enable inferences to be made about the participants’ pre-algebraic thinking. Analysis of the data suggested that ‘look for pattern’, ‘recognise pattern’ and ‘extend pattern’ were among the types of common pre-algebraic thinking inferred from the participants’ verbalisations while solving problems involving geometric patterns.